Environmental degradation does not induce cortisol-measured stress in environmentally aware participants - Rachelle K. Gould; Katrina Moreau; Brendan Fisher; David Gonzalez-Jimenez; Christine Vatovec (PLoS ONE, 2025)
It is well established that exposure to nature can reduce stress – but what if that “nature” is in a degraded state? We suggest a gap in research on nature—stress connections--and attempt to fill that gap. We conducted an experiment to test whether viewing photographs of polluted water would induce stress, as compared to photographs of clean water. In two conditions, we used sets of images that we digitally altered to be equivalent in every way except for the condition of the water. In the polluted-water treatment, all images depicted Harmful Algal Blooms (HABs), also sometimes called cyanobacteria blooms; in the clean-water (control) group, water looked free from HABs. Using a before-after-control-impact design, we tested pre- and post-intervention salivary cortisol to measure response to intervention exposure (i.e., photographs of lakes with or without HABs). We also collected qualitative data related to participants’ reflections on the images they observed, and quantitative data on their connectedness to nature and climate anxiety. Participants recognized the HABs and their negative effects. Yet our hypothesis—that participants who viewed HABs-infested images would have larger increases in cortisol—was not supported, even when considering participants with high and low measures of connectedness to nature and climate anxiety. We discuss possible explanations for the lack of effect found.